Water scarcity in North Cyprus and solar desalination research: a review - Agboola, O. Phillips; Egelioglu, F. (Desalination Publ, 2012)
The shortage of water for domestic and agricultural purposes in North Cyprus (N. Cyprus) is obvious. Various measures have been planned and implemented to increase the supply of water and ensure it is used more efficiently. The backbone of the local economy is agriculture, where the exportation of citrus fruits and potatoes was a significant source of revenue for the government back in the 1960s. The present water crisis on the island however has affected the agricultural sector as this has ceased to be functioning. The water crises implies that there is a shortage of water for irrigation purposes, which has affected the yearly quantity of agricultural produce as vast quantities of arable land suffer from a low yield. Furthermore, seawater has seeped into the aquifers, which have also negatively affected citrus fruit cultivation as most produce die naturally due to the high salt content of the water resources available to them. This paper reviews the sources of water in N. Cyprus and discusses the water scarcity problem in the region. The work also presents solar desalination applications in N. Cyprus to relieve the edible water scarcity.
Keywords: North Cyprus; Solar desalination; Water scarcity; Capacity building; Edible water